5)(a+-a)²= c)(2a+0,5)²-(0,5-2a)²= e)25x²+(7+5x)(7-5x)=

НиколайБлейд НиколайБлейд    1   22.06.2019 00:00    0

Ответы
pozitivtv2905 pozitivtv2905  22.06.2019 00:00
A)   - (a-5)(a+-a)^2= - (a^2+3a-5a-15)- (1-2a+a^2) =          - (a^2 -2a+15 -2a+a^2)=   - a^2 +2 a - 15 -1+2a -a^2 =         -2a^2 + 4a -16= -2  ( a^2 -2 a +8 )   c ) ( 2 a+  0.5)^2 - (  0.5 - 2 a )^2 = ( 0.5 + 2 a )^2 - ( 0 . 5 - 2 a )^2=                 0.25 +2 a + 4 a ^2 -  0.25+ 2 a - 4 a^2= 4 a . e )   25 x ^2 +( 7+5 x) (7-5x )=   25x^2 + 49-25x^2=49
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика